Increased Porphyrins in Primary Liver Cancer Mainly Reflect a Parallel Liver Disease - Jerzy Kaczynski; Göran Hansson; Sven Wallerstedt (Gastroenterology Research and Practice)
Hepatic porphyries have been associated with an increased risk of primary liver cancer (PLC), which on the other hand may cause an increased porphyrin production. To evaluate the role of an underlying liver disorder we analyzed porphyrins in patients with hepatocellular carcinoma (HCC) (n=65), cholangiocellular carcinoma (n=3), or suspected PLC, which turned out to be metastases (n=18) or a benign disorder (n=11). None of the patients had a family history of porphyry or clinical signs of porphyry. Increased aminolevulinic acid or porphyrin values were common not only in patients with PLC (43%) but also in metastatic (50%) and benign (64%) liver disorders. The corresponding proportion for HCC patients with liver cirrhosis (55%) was higher (P<.05) than in those without cirrhosis (17%). We conclude that symptomatic porphyries are unusual in PLC, whereas elevated urinary and/or faecal porphyrins are common, primarily reflecting a parallel liver disease and not the PLC.